Depressive symptoms and quality of life in patients with heart failure and an implantable cardioverter-defibrillator. (19th May 2022) - Zormpas, C; Kahl, K G; Hohmann, S; Oswald, H; Stiel, C; Veltmann, C; Bauersachs, J; Duncker, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Heart failure (HF) is associated with development of depressive symptoms and reduced quality of life (QoL). Patients with HF and an implantable cardioverter-defibrillator (ICD) were evaluated regarding depressive symptoms and QoL. Purpose: Patients with HF and an ICD were prospectively evaluated regarding depressive symptoms and QoL with the intention to elucidate the prevalence of depressive symptoms in this patient cohort and to assess how QoL evolves in the course of the underlying disease. Aim of the analysis is to identify patients in need for supportive care intervention and/or antidepressant therapy. Methods: The present study included 446 patients with HF and an ICD. Depressive symptoms were assessed using the Patient Health Questionnaire 9 (PHQ-9), QoL was evaluated using the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Functional ability and exercise tolerance were assessed at inclusion and after 6 months with help of the 6-minute walking test (6MWT). Results: Patients included in the study had a mean age of 65.8 years and were predominantly male (83.6%), with mostly ischemic (n = 277; 62.1%) or dilated (n = 150; 33.6%) cardiomyopathy. 193 (43.2%) patients had depressive symptoms, of whom 75 patients (16.8%) were classified as moderate to severe depression according to the PHQ-9 at baseline. Depressive symptoms were associated with low QoL independent of NYHA functional class. High NYHA functional class, high PHQ-9 score, age and body mass index (BMI) were associated with a lower 6MWT at enrollment, while depressive symptoms (expressed as higher PHQ-9 score) and age were associated with a lower 6MWT after 6 months. Patients with history of smoking and a higher BMI showed higher PHQ-9 scores after 6 months. Patients under antidepressant medication showed improved PHQ-9 score after 6 months, indicating controlled/treated depression. However, patients with low QoL at inclusion remained with low QoL after 6 months. Conclusion: Depressive symptoms correlate with low QoL and lower long-term functional status in patients with HF and an ICD. Depressive symptoms are associated with smoking and obesity, which themselves are risk factors for a poor prognosis in HF. Only a small fraction of patients with HF and ICD showing depressive symptoms receives appropriate treatment. Assessing depressive symptoms and lifestyle factors should be part of a multimodal treatment plan in patients with HF and an ICD.